Flap endonuclease 1 is involved in cccDNA formation in the hepatitis B virus - Kitamura, Kouichi; Que, Lusheng; Shimadu, Miyuki; Koura, Miki; Ishihara, Yuuki; Wakae, Kousho; Nakamura, Takashi; Watashi, Koichi; Wakita, Takaji; Muramatsu, Masamichi (PLoS pathogens, 2018)
Hepatitis B virus (HBV) is one of the major etiological pathogens for liver cirrhosis and hepatocellular carcinoma. Chronic HBV infection is a key factor in these severe liver diseases. During infection, HBV forms a nuclear viral episome in the form of covalently closed circular DNA (cccDNA). Current therapies are not able to efficiently eliminate cccDNA from infected hepatocytes. cccDNA is a master template for viral replication that is formed by the conversion of its precursor, relaxed circular DNA (rcDNA). However, the host factors critical for cccDNA formation remain to be determined. Here, we assessed whether one potential host factor, flap structure-specific endonuclease 1 (FEN1), is involved in cleavage of the flap-like structure in rcDNA. In a cell culture HBV model (Hep38.7-Tet), expression and activity of FEN1 were reduced by siRNA, shRNA, CRISPR/Cas9-mediated genome editing, and a FEN1 inhibitor. These reductions in FEN1 expression and activity did not affect nucleocapsid DNA (NC-DNA) production, but did reduce cccDNA levels in Hep38.7-Tet cells. Exogenous overexpression of wild-type FEN1 rescued the reduced cccDNA production in FEN1-depleted Hep38.7-Tet cells. Anti-FEN1 immunoprecipitation revealed the binding of FEN1 to HBV DNA. An in vitro FEN activity assay demonstrated cleavage of 5'-flap from a synthesized HBV DNA substrate. Furthermore, cccDNA was generated in vitro when purified rcDNA was incubated with recombinant FEN1, DNA polymerase, and DNA ligase. Importantly, FEN1 was required for the in vitro cccDNA formation assay. These results demonstrate that FEN1 is involved in HBV cccDNA formation in cell culture system, and that FEN1, DNA polymerase, and ligase activities are sufficient to convert rcDNA into cccDNA in vitro.